Explaining the resistomes in a megacity's water supply catchment: Roles of microbial assembly-dominant taxa, niched environments and pathogenic bacteria. (1st January 2023) - Wu, Dong; Zhao, Jue; Su, Yinglong; Yang, Mengjie; Dolfing, Jan; Graham, David W.; Yang, Kai; Xie, Bing
Highlights: Resistome size in the reservoir was comparable to that in sewers. Microbial assembly process significantly influenced dynamics of resistome. Putative resistant bacteria were at the same abundance across the catchment. Putative resistant pathogens greatly contributed to the transmission of ARGs. Intragenomic ARGs frequently transferred to microbial assembly-dominant taxa. Abstract: Antibiotic resistance genes (ARGs) in drinking water sources suggest the possible presence of resistant microorganisms that jeopardize human health. However, explanations for the presence of specific ARGs in situ are largely unknown, especially how their prevalence is affected by local microbial ecology, taxa assembly and community-wide gene transfer. Here, we characterized resistomes and bacterial communities in the Taipu River catchment, which feeds a key drinking water reservoir to a global megacity, Shanghai. Overall, ARG abundances decreased significantly as the river flowed downstream towards the reservoir ( P < 0.01), whereas the waterborne bacteria assembled deterministically (| β NRI| > 2.0) as a function of temperature and dissolved oxygen conditions with the assembly-dominant taxa ( e.g. Ilumatobacteraceae and Cyanobiaceae ) defining local resistomes ( P < 0.01, Cohen's D = 4.22). Bacterial hosts of intragenomic ARGs stayed at the same level across the catchment (60 ∼ 70 genome copies per million reads). Among them, the putative resistant pathogens (e.g. Burkholderiaceae ) carried mixtures of ARGs that exhibited high transmission probability (transfer counts = 126, P < 0.001), especially with the microbial assembly-dominant taxa. These putative resistant pathogens had densities ranging form 3.0 to 4.0 × 10 6 cell/L, which was more pronouncedly affected by resistome and microbial assembly structures than environmental factors (SEM, std-coeff β = 0.62 vs . 0.12). This work shows that microbial assembly and resistant pathogens play predominant roles in prevelance and dissemination of resistomes in receiving water, which deserves greater attention in devisng control strategies for reducing in-situ ARGs and resistant strains in a catchment. Graphic abstract: Image, graphical abstract